Short-term Results of Total Ankle Arthroplasty for End-stage Ankle Arthritis With Severe Varus Deformity. (March 2014) - Sung, Ki-Sun; Ahn, Jungtae; Lee, Keun-Ho; Chun, Tae-Hwan
Background: Many authors have reported that an ankle varus deformity more than 10 to 15 degrees may be the cause of failures in total ankle arthroplasty. Our study aim was to analyze short-term outcomes of total ankle arthroplasty with additional procedures accompanied by more than 20 degrees of varus deformity. Methods: Among the patients who received total ankle arthroplasty for end-stage osteoarthritis between June 2006 and May 2012, 103 cases that were followed for more than 6 months were reviewed. Depending on the degree of varus deformity, 24 cases with more than 20 degrees of coronal deformity were allocated into group A, and 79 cases with less than 20 degrees were allocated into group B. Soft tissue balancing, bony realignment osteotomy, and subtalar arthrodesis were also performed intraoperatively. The American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot scale, visual analogue scale (VAS) for pain, and ankle range of motion (ROM) were analyzed preoperatively and postoperatively. Subjective satisfaction of the patients (excellent, good, fair, or poor) and complications (major or minor) were identified. Results: The average AOFAS and VAS scores significantly improved in both groups ( P < .001), but there was no significant difference between the groups. Patients' subjective satisfaction levels also improved in both groups. Conclusion: Short-term follow-up of total ankle arthroplasty, according to the degree of varus deformity, revealed clinically satisfactory progress in both groups without significant differences. There were no significant differences between the 2 groups in postoperative complications and early implant failures. Level of Evidence: Level III, comparative series.